Psychological Effects of Walking and Relaxed Sitting in Urban Greenspaces During Post-pandemic: A Case Study in Bogor City, Indonesia - Sari, Mona; Fatimah, Indung Sitti; Pratiwi, Prita Indah; Sulistyantara, Bambang (Alanya Üniversitesi, 2023)
The COVID-19 pandemic disrupted the world order from the beginning of 2020 to the end of 2022. The COVID-19 pandemic has had a significant impact on changes in healthy living practices, such as decreased physical exercise and increased stress, compromising psychological well-being. The psychological impacts of walking and relaxing in urban green spaces on IPB University students are investigated in this study. Bogor City Alun-Alun, Sempur Park, and Heulang Park were used for the experiment. Participants completed 15 minutes of walking and relaxed sitting before and after the experiment, and the psychological impacts were assessed using Profiles of Mood States (POMS), State-Trait Anxiety Inventory (STAI), and WHO Quality of Life (WHOQOL-BREF) before and after the experiment. The results indicate that physical activity improves psychological wellness. These findings give scientific evidence for the psychologically relaxing effects of walking and relaxed sitting, as well as recommendations to support the development and construction of therapeutic urban green spaces.